Can we diagnose isolated, exercise-induced heart failure with normal ejection fraction? - Meluzin, Jaroslav; Gregorova, Zdenka; Spinarova, Monika; Panovsky, Roman (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
BACKGROUND: A significant proportion of patients with exertional dyspnea require exercise to diagnose heart failure with normal ejection fraction (HFNEF). METHODS AND RESULTS: In this review article, we evaluate current data on the prevalence, clinical significance and specifically the establishment of a diagnosis of isolated, exercise-induced HFNEF. Despite the unquestioned clinical importance and high prevalence of exercise-induced HFNEF, there are limited and conflicting data on making a diagnosis of exercise-induced HFNEF. This mostly relies on the evidence of exercise-induced elevation in left ventricular filling pressure (LVFP). At present, there is no agreement on the ability of exercise echocardiographic parameteres to predict exercise-induced LVFP elevation. In addition, even invasively measured exercise LVFP faces the problem of defining normal exercise LVFP values. More data and probably new diagnostic approaches are necessary to reliably diagnose exercise HFNEF. CONCLUSIONS: There are conflicting results and significant problems associated with the diagnosis of exercise HFNEF. This review hopefully will encourage further research in this difficult but clinically important area of heart failure.
Keywords: Exercise Test; Exercise; dyspnoe; Humans; lidé; krevní tlak; srdeční selhání; zátěžový test; cvičení; Dyspnea; barevná dopplerovská echokardiografie; Stroke Volume; heart failure with normal ejection fraction; tepový objem; Echocardiography, Stress; Ventricular Dysfunction, Left; Echocardiography, Doppler, Color; Heart Failure; exercise echocardiography; left ventricular filling pressure; Blood Pressure; dysfunkce levé srdeční komory; zátěžová echokardiografie